Incorporated dexamethasone influence in the PEO nanofibers on the proliferation of mesenchymal stem cells - Ghiaee, Armaghan; Farahmand, Mahnaz; Ardeshirylajimi, Abdolreza (Archives of Advances in Biosciences, 2016)
Tissue engineering based on the adipose derived stem cells promote a strong strategy to propagation of bone, cartilage and fat tissues in the three-dimensional scaffolds, fabricated by combining biological materials with suitable and appropriate growth factors. In this study, a PEO scaffold was used to show that mesenchymal stem cells can attach well; the aim of this study was the investigation of dexamethasone (Dex) effect on the proliferation of adipose derived mesenchymal stem cells (AT-MSCs). At first, the Mesenchymal stem cells were isolated from adipose tissue. After culturing the cells and having a good density of the population, the cells were transferred to the scaffold. MTT, DAPI and SEM assays were used for evaluation of biocompatibility of PEO scaffolds, cell survival and also cell alignment of cells cultured on the PEO scaffold in comparison with the PEO-Dex. According to the MTT results, MSCs cell viability on PEO-Dex scaffold showed the significant increase compared with PEO scaffold. SEM result also showed that mesenchymal stem cells were more proliferate and grown on the PEO-Dex scaffolds and were more confluent in comparison with PEO scaffold. Evaluation of DAPI staining indicated significantly significant cell nucleus increase in PEO-Dex compared with PEO group. The results manifested that PEO-Dex could be a suitable scaffold for growing mesenchymal stem cells and is a promising candidate for tissue engineering application.